2019
DOI: 10.1016/j.electacta.2019.134704
|View full text |Cite
|
Sign up to set email alerts
|

Solid electrochemical energy storage for aqueous redox flow batteries: The case of copper hexacyanoferrate

Abstract: All redox flow batteries suffer from low energy storage density in comparison with conventional Li-ion batteries. However, this issue can be mitigated by utilization of solid energy storage materials to enhance the energy storage capacity. In this paper we demonstrate the utilization of copper hexacyanoferrate (CuHCF) Prussian blue analogue for this purpose, coupled with N,N,N-2,2,6,6-heptamethylpiperidinyl oxy-4-ammonium chloride (TEMPTMA) as a soluble redox mediator to target the redox transitions of the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Apart from the high volumetric capacity and capacitive charge transfer kinetics, the organic solid material also has the advantage of potential‐insensitivity to counter ions, which allows facile integration to different systems without the additional potential‐matching process. In conjunction with the ion‐insensitive mediators, we envisage that the PI/2,7‐AQDS electrolyte system can work as a universal anolyte for the previously studied potassium systems, such as the KBr/PB and TEMPTMA/CuHCF …”
Section: Figurementioning
confidence: 99%
“…Apart from the high volumetric capacity and capacitive charge transfer kinetics, the organic solid material also has the advantage of potential‐insensitivity to counter ions, which allows facile integration to different systems without the additional potential‐matching process. In conjunction with the ion‐insensitive mediators, we envisage that the PI/2,7‐AQDS electrolyte system can work as a universal anolyte for the previously studied potassium systems, such as the KBr/PB and TEMPTMA/CuHCF …”
Section: Figurementioning
confidence: 99%
“…Therefore, the mechanisms in the cell are well-known [ 19 ]. Meanwhile, only very few works have studied the kinetics of charge storage in the redox solid materials with redox targeting within the tank [ 13 , 14 , 20 , 21 , 22 , 23 , 24 ]. In an attempt, Li x FePO 4 (0 ≤ x ≤ 1) was coated on a double-layer electrode with an insulating Al 2 O 3 layer and was charged and discharged with the Fc and FcBr 2 + redox couple with a biased electrode [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…They used polyaniline as the redox storage material in iron-containing acidic electrolytes and showed that addition of this solid storage material enhances the energy storage capacity by a factor of three, and also improves the voltage efficiency of the battery [ 12 ]. The concept of charge storage in solid boosters was described in detail with organic (2,2,6,6-Tetramethylpiperidin-1-yl)oxyl (TEMPO) derivative as redox electrolyte and copper hexacyanoferrate as the redox active solid [ 13 ]. Later in 2019, Chen et al [ 6 ] further demonstrated the concept of redox targeting in an aqueous [Fe(CN) 6 ] 4−/3− -based electrolyte with Prussian blue utilized as the redox solid material, and reported an unprecedented volumetric capacity of 61.6 Ah/L relative to other [Fe(CN)6] 4−/3− -based electrolytes for their redox flow battery setup.…”
Section: Introductionmentioning
confidence: 99%
“…Prussian blue and its analogs have previously been used in flow batteries [16][17][18] and provide an average discharge potential of ca 3 V when used in laminated cells as compared to the 3.4 V for LFP while both provide between 150-170 mAh g −1 [19][20][21]. This means that the specific energy calculated using the theoretical capacity and 3 V average discharge potential is close to 500 Wh kg −1 .…”
Section: Introductionmentioning
confidence: 91%